Reversible 2D Phase Transition Driven By an Electric Field: Visualization and Control on the Atomic Scale - Wortmann, B. (2016)
We report on a reversible structural phase transition of a two-dimensional system that can be locally induced by an external electric field. Two different structural configurations may coexist within a CO monolayer on Cu(111). The balance between the two phases can be shifted by an external electric field, causing the domain boundaries to move, increasing the area of the favored phase controllable both in location and size. If the field is further enhanced new domains nucleate. The arrangement of the CO molecules on the Cu surface is observed in real time and real space with atomic resolution while the electric field driving the phase transition is easily varied over a broad range. Together with the well-known molecular manipulation of CO adlayers, our findings open exciting prospects for combining spontaneous long-range order with man-made CO structures such as "molecule cascades" or "molecular graphene". Our new manipulation mode permits us to bridge the gap between fundamental concepts and the fabrication of arbitrary atomic patterns in large scale, by providing unprecedented insight into the physics of structural phase transitions on the atomic scale.